Spatial and Temporal Analysis of Dissolved Oxygen (DO) and Biological Oxygen Demand (BOD) Concentrations in Rawa Pening Lake, Semarang Regency - Handoko, Muhammad; Sutrisno, Alfred Jansen (Jurnal Pendidikan Geografi Gea, 2021)
Rawa Pening Lake are the waterbody which it waters comes from a swamp spring, besides that several rivers empty into Rawa Pening, including Galeh River, Torong River, Panjang River, Muncul River, Parat River, Legi River, Pitung River, Praginan River, and Rengas River. Three problems cause damage to the Rawa Pening Lake ecosystem, namely damage to the water catchment area, damage to the lake border, and water pollution. This study aims to analyze Dissolved Oxygen (DO) and Biological Oxygen Demand (BOD) spatially and temporally due to damage to the lake ecosystem. The method used was Inverse Distance Weighted (IDW), where 12 sample point locations were taken, 10 sample points representing each village (lake inlet and utilization), and 2 sample points representing the center and outlet of the lake. The average DO yield in September 2020 was 6.8 mg / L, then in October 2020 it was 4.65 mg / L and in November 2020 it was 3.04 mg / L. Then the average BOD in September 2020 was 3.16 mg / L, then in October 2020 it was 2.6 mg / L and in November it was 1.53 mg / L, so it can be seen that the DO variable and BOD both decreased from September to November 2020.